TIPS DAN TRIK PENULISAN JURNAL SERTA STRATEGI PUBLIKASI PADA JURNAL TERINDEKS SCOPUS Q3 (BIDANG PENDIDIKAN) - Indah Melati; B. Herawan Hayadi; Aisyah Aisyah; Masruroh Masruroh; Masriah Masriah (STAI Darul Qalam Tangerang, 2026)
Scientific publications in Scopus indexed journals are one of the important indicators in the academic world. However, many researchers have had difficulty penetrating reputable journals, particularly in the Q3 quartile. This article aims to provide practical guidance in the form of tips and tricks in writing scientific journals and publication strategies so that they can be accepted in Scopus Q3 indexed journals. The method used is a literature study of various sources related to academic writing and the scientific publication process. The results of the study show that the success of publication is influenced by the quality of the research, the structure of the writing, the selection of journals, and the scientific communication strategy.